The β2-adrenergic biased agonist nebivolol inhibits the development of Th17 and the response of memory Th17 cells in an NF-κB-dependent manner - Hajiaghayi, Mehri; Gholizadeh, Fatemeh; Han, Eric; Little, Samuel R.; Rahbari, Niloufar; Ardila, Isabella; Lopez Naranjo, Carolina; Tehranimeh, Kasra; Shih, Steve C. C.; Darlington, Peter J. (Frontiers in Immunology, 2024)
Introduction Adrenergic receptors regulate metabolic, cardiovascular, and immunological functions in response to the sympathetic nervous system. The effect of β2-adrenergic receptor (AR) as a high expression receptor on different subpopulations of T cells is complex and varies depending on the type of ligand and context. While traditional β2-AR agonists generally suppress T cells, they potentially enhance IL-17A production by Th17 cells. The effects of pharmacological drugs that count as biased agonists of AR like nebivolol are not completely understood. We investigated the impact of nebivolol on human memory CD4+ T (Th1, Th2, Th17) cells and polarized naive Th17 cells, highlighting its potential for IL-17A suppression via a non-canonical β2-AR cell signaling pathway. Methods The effects of nebivolol were tested on healthy human peripheral blood mononuclear cells, purified memory Th cells, and polarized naive Th17 cells activated with anti-CD3/anti-CD28/anti-CD2 ImmunoCult reagent. IFN-γ, IL-4, and IL-17A, which are primarily derived from Th1, Th2, and Th17 cells, respectively, were quantified by ELISA and flow cytometry. IL-10 was measured by ELISA. Gene expression of RORC, ADRB1, ADRB2, and ADRB3 was evaluated by qPCR. The ADRB2 gene was knocked out in memory Th cells using CRISPR/Cas9. Protein expression of phosphorylated serine133-CREB and phosphorylated NF-κB p65 was assessed by Western blot. Proliferation was assessed by fluorescent dye loading and flow cytometry. Results Nebivolol treatment decreased IL-17A and IFN-γ secretion by activated memory Th cells and elevated IL-4 levels. Nebivolol reduced the proportion of IL-17A+ Th cells and downregulated RORC expression. Unlike the β2-AR agonist terbutaline, nebivolol inhibited the shift of naive CD4+ T cells toward the Th17 phenotype. IL-10 and the proliferation index remained unchanged. Nebivolol-treated β2-knockout memory Th cells showed significant inhibition of β2-AR-mediated signaling, evidenced by the absence of IL-17A suppression compared to controls. Phosphorylation of the NF-κB p65 subunit was inhibited by nebivolol, but CREB phosphorylation was not changed, suggesting a selective transcriptional control. Conclusions The findings demonstrate that nebivolol acts through a β2-AR-mediated signaling pathway, as a distinctive anti-inflammatory agent capable of selectively shifting Th17 cells and suppressing the phosphorylation of NF-κB. This highlights nebivolol’s potential for therapeutic interventions in chronic autoimmune conditions with elevated IL-17A levels.